2023
DOI: 10.3390/ani13071140
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Canine Ergonomic Abdominal Simulator for Training Basic Laparoscopic Skills in Veterinarians

Abstract: The validity of the CALMA Veterinary Lap-trainer simulator (CVLTS) for training basic veterinary laparoscopic skills was assessed and compared to a simple collapsible mobile box trainer. Ten veterinarian surgeons with no experience in laparoscopic surgery and four experts with at least two years of experience in minimally invasive surgery (MIS) were included. The training curriculum included object transfer, non-woven gauze cutting with curved scissors, and interrupted and continuous intracorporeal sutures, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…We provide evidence on the importance of practicing repeated laparoscopic surgical skills for LOE in dogs using the CVLTS and reconstituted reproductive tissues, which provide the apprentices with the natural texture and conditions of the uterine and ovarian tissues. This model also provides a more accurate ergonomic device for training these and other laparoscopic surgical skills in dogs as reported elsewhere [24,25]. Our study proposes an advanced training plan to develop the laparoscopic skills required to perform ovariohysterectomy in female dogs.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…We provide evidence on the importance of practicing repeated laparoscopic surgical skills for LOE in dogs using the CVLTS and reconstituted reproductive tissues, which provide the apprentices with the natural texture and conditions of the uterine and ovarian tissues. This model also provides a more accurate ergonomic device for training these and other laparoscopic surgical skills in dogs as reported elsewhere [24,25]. Our study proposes an advanced training plan to develop the laparoscopic skills required to perform ovariohysterectomy in female dogs.…”
Section: Discussionmentioning
confidence: 66%
“…The construction of the simulator was based on a mold of a large breed canine abdomen, in which the Objective structured assessment of technical skill (OSATS) and GOALS evaluation systems and a surgical-procedure-specific scale according to the surgical procedure evaluated were incorporated. These experiments were performed successively to evaluate and validate basic skills [25] and advanced skills in laparoscopic surgery [25]. Similarly, the main purpose was to evaluate the transmission of surgical skills with the total laparoscopic gastropexy model after completing the training in the simulator and evaluating the performance of trainees in real conditions in TLG in the porcine model in vivo (manuscript submitted).…”
Section: Introductionmentioning
confidence: 99%
“…The conclusion of the study was that the CLVTS was accepted as a realistic and useful tool for teaching and training intracorporeal suturing for TLG [16]. In a more recent paper regarding the face, content, construct, and concurrent validity assessed by four experts and ten non-experts, the authors showed that the CLVTS can be successfully used also for basic skills training in MIS [17]. The Objective Structured Assessments of Technical Skills (OSATS) and Hands Movement Assessment System (HMAS) were used to evaluate the surgical skills.…”
Section: The Calma Veterinary Lap-trainer Composite Simulator (Clvts)mentioning
confidence: 97%